2011
DOI: 10.1002/app.34385
|View full text |Cite
|
Sign up to set email alerts
|

Compatibilization of recycled poly(ethylene terephthalate) and polypropylene blends: Effect of compatibilization on blend toughness, dispersion of minor phase, and thermal stability

Abstract: Blending of recycled polyethylene terephthalate (RPET) from waste bottles with polypropylene (PP) was performed in an attempt to enhance the processability of RPET. The idea of blending RPET with PP sprouted from the intention of recycling PET bottles together with their PP‐based caps. Therefore, preliminary blending of RPET with neat PP (RPET/PP) was performed at various PP and compatibilizer contents. Morphological analyses on the extruded pellets of uncompatibilized blends indicate that the PP particle size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…Incompatibility between the rPET and polyolefin leads to gross phase separation and poor mechanical properties of the blend [10]. For this reason, compatibilizers such as maleic anhydride polyethylene (MAPE) and maleic anhydride polypropylene (MAPP) are used to improve the compatibility between rPET and polyolefin [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Incompatibility between the rPET and polyolefin leads to gross phase separation and poor mechanical properties of the blend [10]. For this reason, compatibilizers such as maleic anhydride polyethylene (MAPE) and maleic anhydride polypropylene (MAPP) are used to improve the compatibility between rPET and polyolefin [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been performed to reduce these physical characteristic problems of rPET, such as the blending of rPET with either biodegradable or non‐biodegradable polymers, such as poly(butylene adipate‐ co ‐terephthalate) (PBAT), polypropylene (PP), ethylene octene copolymer, polycarbonate, and acrylonitrile butadiene styrene terpolymer . Srithep et al reported an increase in the toughness and molecular weight of rPET by the addition of PBAT and chain extender, respectively, and so the mechanical properties and moldability of the rPET were improved .…”
Section: Introductionmentioning
confidence: 99%
“…Srithep et al reported an increase in the toughness and molecular weight of rPET by the addition of PBAT and chain extender, respectively, and so the mechanical properties and moldability of the rPET were improved . Inoya et al also added PP to rPET to improve the processability, mechanical performance, and degradation temperature of the rPET . Moreover, some inorganic fillers, such as silicon nitride , glass fibers , and nanoclay , have also been used to improve the physical properties of rPET.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, polymer mixtures usually need a compatibilizer to improve the interfacial adhesion, reduce surface tension and promote morphological stability of the blend 2,3 . Poly (ethylene terephthalate) (PET) is recognized as one of the most versatile engineering plastics; it is mainly used in soft drink bottles and textile industry, being one of the most disposed packing materials 4 . The increasing economic and environmental value of the PET recycling industry has caused interest worldwide.…”
mentioning
confidence: 99%